2008
DOI: 10.4219/jaa-2008-812
|View full text |Cite
|
Sign up to set email alerts
|

Explaining Relationships Among Student Outcomes and the School's Physical Environment

Abstract: This descriptive study investigated the possible effects of selected school design patterns on third-grade students' academic achievement. A reduced regression analysis revealed the effects of school design components (patterns) on ITBS achievement data, after including control variables, for a sample of third-grade students drawn from 24 elementary schools. The sample means on the ITBS per school represented approximately 1,916 third-grade students. The independent variable set for developing a possible expla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(63 citation statements)
references
References 10 publications
1
54
0
5
Order By: Relevance
“…The study of 3rd graders included measures for instructional neighborhoods and large group meeting places. Statistically significant relationships between the design measures and scores on the ITBS were found for all composite measures [47,48].…”
Section: Building Feature Categorymentioning
confidence: 86%
See 1 more Smart Citation
“…The study of 3rd graders included measures for instructional neighborhoods and large group meeting places. Statistically significant relationships between the design measures and scores on the ITBS were found for all composite measures [47,48].…”
Section: Building Feature Categorymentioning
confidence: 86%
“…Research conducted by Tanner [47,48] and Barrett et al [43,45], using composite measures of different building features identified several interior design elements that have significant effects on student performance. Measures of design elements used in Tanner studies were from a larger instrument designed for assessing physical learning environments by researchers at the SDPL (University of Georgia's School Design and Planning Laboratory's).…”
Section: Building Feature Categorymentioning
confidence: 99%
“…From lighting to air quality to temperature, the ways in which a classroom is physically designed, organized, and managed all impact students' learning. Classrooms with more natural light, for example, tend to have students who perform better academically (Tanner, 2008), while the optimal temperature for learning is between 68 and 74 degrees Fahrenheit (Earthman, 2004). The ways in which the classroom furniture is organized signals appropriate communication with the instructor and peers (Burgess & Kaya, 2007).…”
Section: Learning Environmentsmentioning
confidence: 99%
“…Tanner (2008) takes the approach that schools should be considered holistically, not simply the classrooms in which teaching takes place. Places for formal and informal meetings are essential contributors to learning as much as they are social spaces, for learning is a social process.…”
Section: Evidence In Educational Contextsmentioning
confidence: 99%